A study on occupational safety and health among workers at a tertiary care hospital at south India - K., Minikumary C.; Pillai, Jawahar S. K.; Mondal, Ramkrishna (International Journal Of Community Medicine And Public Health, 2022)
Background: Occupational safety and health (OSH) is important for moral, legal and financial reasons for any organization. Aims of the OSH programs include encouragement of a safe and healthy work environment. This study aimed to study the occupational safety and health among healthcare workers at a tertiary care hospital. Methods: The cross-sectional descriptive type of study in a tertiary care hospital at south India. In this cross-sectional descriptive study, 120 health care workers were subjected to a pre-tested questionnaire. Along with questionnaire and interview method, inspection round and review of Incident register with 32 case reports were used as secondary source of data. Simple statistical methods were used to analyse the data. Results: Risk assessment shows out of physical hazards (n=120) 21% Musculoskeletal disorder followed by 13% burns and 10% strain due to uncomfortable posture. Chemical hazards identified were 8% dust, 7% chemical inhalation and 6% sterilization gases. Biological hazards were 12% needle stick injury, 11% splash and 5% sharp injury (n=120). Equipment hazards reported more among nurses. Among psychosocial hazards shift duty stress was highest (17%). Incident register showed slips/falls (28%), equipment hazards (23%) and needle stick injury (19%) as most common hazards (n=32). Conclusions: The percentage of occupational hazards in the study setting was less compared to national and international standards available. Risk assessment should be done periodically and periodic training and awareness programs for hospital employees directly influences on the quality of patient care.